Perbandingan Aspek Motivasi Belajar, Literasi Terhadap Teknologi, dan Kolaborasi Siswa Sebelum dan Sesudah Mengikuti Pembelajaran Dalam Jaringan pada Mata Pelajaran Pemrograman di SMKN 12 Malang - Afrizal Aldiansyah Putra; Admaja Dwi Herlambang; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Learning is the main activity in the whole educational process in schools. Because learning is done at home (online), the success of learning will be disrupted, especially in the aspects of learning motivation, technological literacy, and collaboration between students. The purpose of this study is to compare aspects of learning motivation, technological literacy, and student collaboration when they are still doing face-to-face learning, compared to online learning. This study used descriptive qualitative method. Interviews with students and teachers relate to these three aspects. Then the analysis technique uses the Miles and Huberman method, namely collecting data, reducing research data, and presenting data. Based on the results of interviews that have been conducted, there are several keywords that appear in the research. Among them are limited internet quota, and also network problems. The conclusion in this study is that most students at SMK Negeri 12 Malang feel they tend to experience a decrease in learning motivation in terms of attendance and doing assignments, compared to when they were still in school face to face. Then for technological literacy, most students admitted that they only knew about learning applications when distance learning took place and not a few had difficulties in operating. Meanwhile, in the aspect of collaboration between students, most of the students admitted that they had difficulty communicating with other students.